Analitični hierarhični proces kot orodje za ocenjevanje in izbiro projektov - Palčič, Iztok (Projektna mreža Slovenije, 2009)
This paper presents several methods for evaluating and selecting projects. A special focus is on Analytical Hierarchy Process (AHP) method that is becoming increasingly important tool in different decision-making situations. We have used this method in project management and developed a project evaluation and selecting process. We have also developed a simple application in MS Excel that helps with calculating projects' total priority grade.
Keywords: management; podjetja; poslovna strategija; projekti; projektno vodenje; vodenje